Reply to “Comment on an article by Gonzaga et al. J Am Ceram Soc. 2020;103:6280-6288” - Gonzaga, Luiziana A. [UNESP]; Santana, Vinicius T.; Bernardi, Maria Inês B.; Hrubý, Jakub; Neugebauer, Petr; Mesquita, Alexandre [UNESP] (Wiley, 2021)
In the “Comment on article by Gonzaga et al. J Am Ceram Soc. 2020;103:6280-6288”, Paparazzo argues that the estimated value of Ce3+ amount in our CeO2 samples through X-ray photoelectron spectroscopy (XPS) analysis is ~10% and there is no dependence on the annealing temperature or Pr-doping. However, a comparison of our XPS Ce 3d spectra with the reference presented by that author reveals characteristics in these spectra of higher at.%Ce3+ being consistent with values of around 24%. Furthermore, the intensity of the absorption in the region around the feature assigned as v′ in XPS Ce 3d spectra decreases as a function of Pr-doping and annealing temperature, confirming different at.%Ce3+ for the samples due to these aspects.
Keywords: cerium/cerium compounds; nanostructures; pigment; rare earths; XPS